Monitoring health and health behaviors among adolescents in Central Catalonia: DESKcohort protocol - Judit Rogés; Helena González-Casals; Marina Bosque-Prous; Cinta Folch; Joan Colom; Jordi Casabona; Gemma Drou-Roget; Ester Teixidó-Compañó; Esteve Fernández; Carmen Vives-Cases; Albert Espelt (Gaceta Sanitaria, 2023)
The objective of the prospective cohort study (the DESKcohort project) is to describe and monitor health, health behaviors, and their related factors among 12 and 19-year-old adolescents schooled at centers of Compulsory Secondary Education or post-compulsory secondary education in Central Catalonia, considering social determinants of health. The DESKcohort survey is administered biannually between the months of October and June, and the project has been running for three years. We have interviewed 7319 and 9265 adolescents in the academic years 2019/20 and 2021/22, respectively. They responded a questionnaire created by a committee of experts, that included the following variables: sociodemographic factors, physical and mental health, food, physical activity, leisure and mobility, substance use, interpersonal relationships, sexuality, screen use and digital entertainment, and gambling. The results are presented to educational centers, county councils, municipalities, and health and third sector entities to plan, implement, and evaluate prevention and health promotion actions that address the identified needs. Resumen: El objetivo de este estudio prospectivo de cohortes (proyecto DESKcohort) es describir y monitorizar la salud, los comportamientos de salud y sus factores asociados en los adolescentes de entre 12 y 19 años escolarizados en centros de Educación Secundaria Obligatoria o secundaria posobligatoria de la Cataluña Central, considerando los determinantes sociales de la salud. La encuesta DESKcohort se realiza bianualmente, entre los meses de octubre y junio, y el proyecto lleva 3 años en marcha. Se ha entrevistado a 7319 y 9265 adolescentes en los cursos 2019/20 y 2021/22, respectivamente. Respondieron un cuestionario creado por un comité de expertos, que incluía las siguientes variables: sociodemográficas, salud física y mental, alimentación, actividad física, ocio y movilidad, consumo de sustancias, relaciones interpersonales, sexualidad, uso de pantallas y entretenimiento digital, y juegos de azar. Los resultados son presentados a los centros educativos, las diputaciones, los municipios y las entidades sanitarias y del tercer sector para planificar, implementar y evaluar acciones de prevención y promoción de la salud que aborden las necesidades identificadas.